Violence assessment and intervention: the practitioner's handbook - Cawood, James S. (Routledge, 2020)
"Violence Assessment and Intervention: The Practitioner's Handbook, now in its third edition, provides a proven methodology, grounded in the current empirical research and the authors' experience in successfully assessing and managing thousands of cases in a variety of contexts and environments, for analyzing concerning behaviors and potential threatening situations and taking action in these challenging, dynamic environments before tragedy occurs. Threat and violence assessment and management is an essential process in reducing violence and its consequences. The ongoing challenge for those assessors, particularly in common workplace environments (e.g. educational settings, public agency settings, and business settings), is applying the applicable behavioral science research in a practical and effective manner to maximize safety. The book begins by demonstrating the threat and violence assessment process from the point of the initial call and proceeds through the steps that quantify the situation and determine the appropriate response. The next section covers information gathering, victimology, and formulas and tools for risk assessment. Finally, the book explores organizational influences, school violence, ethics, security and consultation issues; the formation and running of threat management teams, and relevant laws related to violence assessment. This book is a valuable reference for human resource professionals, security professionals, mental health practitioners, law enforcement personnel, and lawyers who are members of threat assessment teams, provide threat and violence assessment and management consultations, as well as expert witnesses in cases involving workplace violence, school violence, security negligence, or wrongful employment or school disciplinary actions related to threatening or violence concerns"--